Study protocol for a multicentre comparative diagnostic accuracy study of tools to establish the presence and severity of peripheral arterial disease in people with diabetes mellitus: the DM PAD study. Issue 11 (3rd November 2022) - Normahani, Pasha; Burgess, Laura; Norrie, John; Epstein, David Mark; Kandiyil, Neghal; Saratzis, Athanasios; Smith, Sasha; Khunti, Kamlesh; Edmonds, M; Ahluwalia, Raju; Coward, Trusha; Hartshorne, Tim; et al.
Abstract : Introduction: Peripheral arterial disease (PAD) is a key risk factor for cardiovascular disease, foot ulceration and lower limb amputation in people with diabetes. Early diagnosis of PAD can enable optimisation of therapies to manage these risks. Its diagnosis is fundamental, though challenging in the context of diabetes. Although a variety of diagnostic bedside tests are available, there is no agreement as to which is the most accurate in routine clinical practice. The aim of this study is to determine the diagnostic performance of a variety of tests (audible waveform assessment, visual waveform assessment, ankle brachial pressure index (ABPI), exercise ABPI and toe brachial pressure index (TBPI)) for the diagnosis of PAD in people with diabetes as determined by a reference test (CT angiography (CTA) or magnetic resonance angiography (MRA)). In selected centres, we also aim to evaluate the performance of a new point-of-care duplex ultrasound scan (PAD-scan). Methods and analysis: A prospective multicentre diagnostic accuracy study (ClinicalTrials.gov Identifier NCT05009602 ). We aim to recruit 730 people with diabetes from 18 centres across the UK, covering primary and secondary healthcare. Consenting participants will undergo the tests under investigation. Reference tests (CTA or MRA) will be performed within 6 weeks of the index tests. Imaging will be reported by blinded consultant radiologists at a core imaging lab, using a validated scoring system, which will also be used to categorise PAD severity. The presence of one or more arterial lesions of ≥50% stenosis, or tandem lesions with a combined value of ≥50%, will be used as the threshold for the diagnosis of PAD. The primary outcome measure of diagnostic performance will be test sensitivity. Ethics and dissemination: The study has received approval from the National Research Ethics Service (NRES) (REC reference 21/PR/1221). Results will be disseminated through research presentations and papers. Trial registration number: NCT05009602 .